Peripheral Arterial disease and Cardiovascular Mortality in Type-2 Diabetes Mellitus - Esa, Dekta Filantropi; Prahasary, Adelia Nova; Tahapary, Dicky L.; Yunir, Em (UI Scholars Hub, 2019)
Peripheral arterial disease (PAD) is one of the macrovascular complications of type 2 diabetes mellitus (T2DM), which increases the risk of cardiovascular mortality. Ankle-brachial index (ABI) is one of the simple and widely available tool to diagnose PAD. The authors aim to find out the cardiovascular mortality in T2DM patient with PAD. Bundo et al. study found HR 2.45 (95% CI: 0.84 to 7.17). Mostaza et al. study reported HR 1.64 (95% CI: 0.64 to 4.49). Aboyans et al. study declared HR 2.21 (95% CI: 1.16 to 4.22). Mohammedi K et al. claimed HR 1.35 (95% CI: 1.15 to 1.60). Quiles et al. found HR 6.61 (95% CI: 2.47 to 17.72). Mueller et al. study reported RR 3,53 (95% CI: 1.80 to 6.91). Mueller et al. study reported RR 4,06 ( 95% CI: 2.67 to 6.18). In conclusion, the mortality risk in T2DM patients with PAD is higher compared to those without PAD. Moreover, an ankle-brachial index can be used as an independent stratification tool to predict the risk of cardiovascular mortality